Protein profile of Andrographis paniculata to salinity treatment - Hossain, Md Sanower; Muhamad Bunnori, Noraslinda; Phang, Ing Chia (2014)
Salinity is one of the environmental factors that limit growth, development and agricultural productivity in plants. Andrographis paniculata, a medicinal plant commonly used to treat diabetes and hypertension, is a salt-sensitive plant. In order to better understand salinity stress responses in A. paniculata, protein profiling using a two-dimensional polyacrylamide gel electrophoresis (2DGE) was performed. A. paniculata was grown and subjected to 0, 20.55, 41.1, 66.75 and 92.4 mM NaCl in a hydroponic culture. Total protein was extracted from the leaves of A. paniculata using chloroform-trichloroacetic acid-acetone method with 4-(2- hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) buffer. From Bradford assay and SDS-PAGE, the extracted protein was found to be a good quantity and quality by comparing with standard protein (Bovine serum albumin) and protein marker, respectively. Protein extracts from A. paniculata treated with 41.1 mM NaCl and control were separated using 2DGE. A total of 153 and 166 protein spots were detected in 41.1 mM NaCl treatment and control, respectively. From PDQuest analysis, 91 protein spots were found to be differentially expressed. Among these protein spots, 41 were up-regulated, 37 were down-regulated and 13 became absent. Database search (i.e. SWISS-PROT) using predicted Mr and pI revealed that proteins that were up-regulated by more than 10-fold are Agamous-like MADS-box protein AGL97, NAP1-related protein 2, Putative two-component response regulator-like APRR8, 2 unknown proteins, and proteins that were down-regulated by more than 10-fold are Probable 26S proteasome complex subunit sem1-2, Peroxidase 22, Methylsterol monooxygenase 1-3, Ent-kaurene oxidase, chloroplastic, La-related protein 1C, 2 unknown proteins. These regulated proteins belong to several functional categories including stress and defense, energy, metabolism, protein synthesis and degradation, cell structure, and signal transduction. Identification of protein using MALDI-TOF is currently underway. The present work provides a new insight into salt stress responses in A. paniculata.